Pengaruh Sales Promotion dan Shopping Lifestyle terhadap Impulse Buying Konsumen pada Marketplace Lazada di Kota Malang - Faiqotul Hasanah; Baroroh Lestari (GLOBAL SCIENTS PUBLISHER, 2025)
Examining how purchasing habits and sales promotions affect impulsive purchases on the Lazada marketplace is the goal of this research. Explanatory research methodology was used in this quantitative investigation. Questions and paperwork were the methods utilized to obtain the data. In Jatimulyo Village, Lowokwaru District, Malang City, 100 respondents from the Lazada marketplace were selected by the purposive sample technique. This study's findings indicate that impulse buying on the Lazada marketplace is positively impacted, albeit partially and simultaneously, by sales promotions and shopping habits.It is necessary to optimize sales promotion strategies by providing price discounts and addling more prizes so that consumer impulse buying increases. Additionally, it is necessary to optimize the lifestyle shopping strategy by providing more attractive fashion advertisements so that the consumer impulse buying increases.